P300 Repetitive magnetic stimulation reverses the synaptic phenotype of cultured rat CA1 pyramidal neurons in a maternal immune activation model of schizophrenia. Issue 3 (March 2017) - Galanis, C.; Lenz, M.; Aliane, V.; Funke, K.; Vlachos, A.
Abstract : Question: Gestational infection is a risk factor for psychiatric disorders. Accordingly, preclinical models of maternal immune activation (MIA) have been developed to study effects of gestational infection on neural and behavioral dysfunction in the offspring. Considering that early pre-symptomatic stages of schizophrenia may affect hippocampal circuits, we here established a hippocampal 'organotypic in vitro MIA model' based on the well-established polyinosinic-polycytidylic acid [Poly(I:C)] model of schizophrenia. We studied alterations in synaptic neurotransmission and tested whether repetitive magnetic stimulation (rMS) influences alterations in synaptic excitation/inhibition-balance in this model. Methods: Entorhino-hippocampal slice cultures were prepared from litters of Poly(I:C) or vehicle-only injected pregnant dams. The effects of 10 Hz rMS on MIA associated alterations in synaptic properties were assessed in CA1 pyramidal neurons using whole-cell patch clamp recordings. Results: Our experiments disclose an increase in inhibitory synaptic strength, while excitatory synapses on CA1 neurons are not changed in slice cultures prepared from Poly(I:C) offspring. This difference is also observed in cultures prepared from cross-fostered animals, thus confirming that gestational infection triggers the synaptic phenotype. Since our recent work has demonstrated that 10 Hz rMS can shift synaptic excitation/inhibition-balance toward excitation, we employed this rMS protocol to test whether we can influence the synaptic phenotype in the Poly(I:C) group. Indeed, 10 Hz rMS reversed the increased inhibitory synaptic strength without affecting excitatory synapses in MIA slice cultures. Conclusion: These results suggest that rMS may exert positive effects under pathological conditions by restoring physiological synaptic excitation/inhibition-balance. We propose that 'organotypic in vitro MIA models' may serve as preclinical drug and intervention screening assays to evaluate and learn more about rTMS-based treatment strategies in psychiatric diseases associated with gestational infection. (Supported by Federal Ministry of Education and Research, Germany (BMBF, GCBS-WP1: 01EE1403B).).